The Effect of Speakmate Toward Students’ Speaking Perfomance at English Department of Dayanu Ikhsanuddin University - Yunus; Abidin Pammu; Nasmilah (Hasanuddin University, 2021)
The problem in this research are: Does speakmate influence students speaking performance at English Department, and how is students’ self-confidence of having speakmate on students’ speaking performance. This research aims to know the effect of speakmate on students’ speaking performance and know students’ self-confidence to speak mate. This research was a quantitative approach by applying experimental method of quasi-experimental design. The population was all of eight-semester college students , class C and class D who enrolled in academic year 2017/2018. The sample was taken by the. The researcher used purposive sampling, 10 students in experimental group and 10 students in the control group. The intrument used in this research was pretest and posttest in experimental group and control group in the form of speaking test. The finding indicated that the mean score of paired students with their speakmate of the experimental group in pretest is 60.66 in moderate category and the mean score in posttest is 77.33 in the good category. while in the control group, the mean score in pretest is 60.66 in moderate category an the mean score in posttest is 64.66 in the moderate category. The result of hypothesis analysis indicated that tcount is 2.905 is more significant than t-table is 2.101. it means that Ho is rejected and H1 is accepted. Based on the calculation of the t-test above, it can be concluded that speakmate influence students speaking performance. Majority of students show their agreements that speakmate influence students’ speaking performance.